Adolescents with Chronic Illnesses: School Absenteeism, Perceived Peer Aggression, and Loneliness - Rosalyn H. Shute; Christine Walsh (The Scientific World Journal)
Frequent school absence is often cited as a risk factor for peer relationship problems in youngsters with chronic illnesses, but this assumption has not been subjected to quantitative empirical examination. This issue was examined in the present study by exploring the relationship between school absenteeism, peer aggression, and loneliness in adolescents with chronic illnesses. Forty-one adolescents with chronic illnesses completed a modified version of the Direct and Indirect Aggression Scale and the Asher Loneliness Scale. Details of school absences and hospitalizations were obtained from parents and school and hospital records. No evidence was found to support the notion that peer aggression and loneliness are related to absenteeism, but social aggression (for both boys and girls) and verbal aggression (more markedly for girls) were associated with loneliness. Of the group, 19% reported experiencing verbal aggression and 12% social aggression at least weekly; informal qualitative data suggesting that such aggression is often related to limited sporting ability and appearance. Interventions at both the individual and school community level are warranted.